2011
DOI: 10.1002/pssc.201000533
|View full text |Cite
|
Sign up to set email alerts
|

Graphene segregation on Ni/SiO2/Si substrates by alcohol CVD method

Abstract: We performed graphene synthesis on Ni films using ethanol gas in this report. A size of a segregated graphene is responsible for a size of underlying Ni catalyst according to evaluations of Raman spectroscopy, FE‐SEM and AFM. A distribution of graphene layer number is also observed because of a surface roughness of Ni. A domain size of segregated graphene networks depends on the size of underlying Ni grains. Comparing plots of W2D as a function of IG/I2D between a segregated graphene on a Ni film and exfoliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It was reported that the temperature and catalysts are two vital factors for the formation of graphene in a chemical vapor deposition (CVD) system. Thus, we focus on the flash temperature rise and catalysts during sliding. On the one hand, the flash temperature rise could be calculated as the followed formula: where Δ T is the flash temperature rise between two contact interfaces, μ is the average friction coefficient, and L is the applied load along the perpendicular direction between contact interfaces and equals to 113 N (for the conversion relationships, see Figure S1); the linear speed of υ equals to 1.1 m/s, a is the contact radius of the real contact region, and K YG8ball is the thermal conductivity of the YG8 ball (75 W/m K) .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the temperature and catalysts are two vital factors for the formation of graphene in a chemical vapor deposition (CVD) system. Thus, we focus on the flash temperature rise and catalysts during sliding. On the one hand, the flash temperature rise could be calculated as the followed formula: where Δ T is the flash temperature rise between two contact interfaces, μ is the average friction coefficient, and L is the applied load along the perpendicular direction between contact interfaces and equals to 113 N (for the conversion relationships, see Figure S1); the linear speed of υ equals to 1.1 m/s, a is the contact radius of the real contact region, and K YG8ball is the thermal conductivity of the YG8 ball (75 W/m K) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to methods using the gas precursor to produce graphene, a wide range of carbon feedstocks has been reported in literature, such as poly(methylmethacrylate) (PMMA), SU8-2002 photoresist, benzene, ethanol, and other carbon sources [ 165 , 166 ]. When SU8-2002 photoresist is used on Ni foil with annealing at 1000 °C in an ambient mixture of He and H 2 gas, high-quality graphene is synthesized [ 165 ].…”
Section: Synthesis Of Carbon Nanomaterialsmentioning
confidence: 99%
“…Synthesis of graphene from ethanol on a nickel substrate has also been demonstrated. 11,12 In previous studies of graphene growth on copper from an ethanol precursor, various authors explored temperature ranges lower than those usually reported for methane-assisted CVD: 650−850 °C9 and 900 °C. 10 To date, graphene growth at high temperature, namely, above 1000 °C, has never been investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Their results suggested that graphene films grown from ethanol contain lower defect densities and higher crystallinity and uniformity than those synthesized from pentane. Synthesis of graphene from ethanol on a nickel substrate has also been demonstrated. , …”
Section: Introductionmentioning
confidence: 99%